PEMBEKALAN P3K CABANG BULUTANGKIS PADA GURU PJOK KECAMATAN TAMAN SARI JAKARTA BARAT - Khaeroni; Hidayat Humaid; Tirto Apriyanto (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract Students are not required to excel, but the education unit (school) provides a forum for students to movefreely and get to know and learn several sports, one of which is badminton. The learning process of PJOK,especially badminton material, is quite closely related to injuries. Like this, it is certainly very dangerousif an injury occurs to students, it can have a bad impact on their physical and mental well-being, especiallyfor children at the elementary school (SD) education level because the child is still in the growth anddevelopment stage so it must be given. The solution offered from the above problems is to provide anunderstanding of P3K technical activities in the badminton branch for PJOK teachers and provide trainingand assistance in P3K technical activities in the badminton branch for PJOK teachers. Service activitiesare carried out by providing knowledge both theoretical and practical about PJOK teachers' knowledgeabout P3K Badminton Branch Debriefing at PJOK Teachers, Taman Sari District, West Jakarta.Community service activities have been carried out well and received enthusiastic responses from theparticipants of the activity. This is evident from the participation rate of activity participants of 81.08% ofthe total PJOK teachers in Taman Sari District, West Jakarta. The level of satisfaction of PJOK teachersin Taman Sari District, West Jakarta, for this service activity is very high, which is 85.83%. AbstrakPeserta didik tidak dituntut untuk berprestasi namun satuan pendidikan (sekolah) memberikan wadahkepada peserta didik untuk keleluasaan bergerak serta mengenal dan belajar beberapa cabang olahraga salahsatunya adalah cabang bulutangkis. Proses pembelajaran PJOK khususnya materi bulutangkis cukup eratkaitannya dengan cedera. Seperti hal ini tentu sangat berbahaya jika cedera terjadi kepada peserta didik, haltersebut dapat berdampak buruk terhadap fisik dan juga mentalnya, apalagi untuk anak pada jenjangpendidikan Sekolah Dasar (SD) karena anak masih dalam tahap pertumbuhan dan perkembangan sehinggaharus diberikan. Solusi yang ditawarkan dari permasalahan di atas adalah memberikan pemahamankegiatan tehnis P3K pada cabang bulutangkis bagi guru-guru PJOK serta memberikan pelatihan danpendampingan kegiatan tehnis P3K pada cabang bulutangkis bagi guru-guru PJOK. Kegiatan pengabdiandilakukan dengan pemberian pengetahuan baik teori maupun praktek tentang pengetahuan guru PJOKtentang Pembekalan P3K Cabang Bulutangkis Pada Guru PJOK Kecamatan Taman Sari Jakarta Barat.Kegiatan pengabdian kepada masyarakat telah terlaksana dengan baik dan mendapatkan respon yangantusias dari para peserta kegiatan. Hal ini terbukti dari tingkat partisipasi peserta kegiatan sebesar 81,08%dari total guru PJOK di Kecamatan Taman Sari Jakarta Barat. Tingkat kepuasaan guru PJOK KecamatanTaman Sari Jakarta Barat terhadap kegiatan pengabdian ini sangat tinggi yaitu sebesar 85,83%.Kata Kunci: Guru PJOK, Sekolah Dasar, P3K